Analisis Risiko Keselamatan dan Kesehatan Kerja (K3) pada Proses Bunker Kapal Tunda (Tug Boat) di PT. Pelindo Marine Service - Muh. Dzaky Murtadha; Naniek Ratni (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The importance of K3 in the tugboat bunkering process is not only limited to safety aspects, but also has a direct impact on ship readiness. Implementing good K3 ensures that bunkering is carried out in accordance with existing procedures. In addition, implementing good K3 will support the operations of ships that have been bunkered so that the ship can continue to operate effectively in supporting various maritime transportation needs. The research method used is the HIRADC (Hazard Identification Risk Assessment Determining Control) method. HIRADC is a method of risk management. For data collection techniques in this research, field observations, interviews and company data were used. In this data analysis and discussion, an analysis of the data processing that has been carried out will be carried out, namely identifying potential risk values ​​and considering the risk ranking to determine priorities and methods of control. After the data analysis and discussion, the next step is to draw conclusions from the data analysis that has been carried out. In the process of filling a ship with fuel (bunker), various dangers or risks can arise throughout the stages of the activity. Hazard identification involves recognizing and documenting the various potential elements that could cause an accident or health problem. For example, slipping, being pinched, being hit by a fuel pump hose during the bunkering process are also aspects that need to be identified as dangers. The work activity identified in this research is the activity of filling the ship with fuel (bunker), then carrying out a risk assessment of the work activity, then determining the necessary hazard and risk controls with the aim of preventing accidents. Data processing will be carried out using the HIRADC method. This step will later become input and suggestions that can be implemented at PT Pelindo Marine Service as a reference for determining steps to deal with work accidents that occur. The importance of identifying hazards in ship bunkering activities is to develop effective prevention strategies and ensure that appropriate safety measures are taken. For example, if hazards related to slips and falls are identified, measures such as special training for operators, use of personal protective equipment (PPE), and strict implementation of standard operating procedures (SOPs) can be impl